PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA PT CENTRAL GLOBAL - Wulandari, Nada; Evyanto, Winda (SCIENTIA JOURNAL, 2022)
This study aims to examine whether there is an effect of service quality, product diversity and promotion on consumer satisfaction of PT Central Global. The research was conducted using quantitative methods. The population used is PT Central Global 100 consumers. The sample of this study amounted to 100 consumers with saturated sampling technique, so the sampling in this study was the whole of the population. The method of data collection is a questionnaire. The effect test uses multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis test in this study uses (t test) and (F test) using SPSS 25 software program. The results of the coefficient of determination (R2) obtained from the quality variable service, product diversity and promotion have an effect of 59.7% on consumer satisfaction. The results of multiple linear regression test show that service quality has an effect of 0.225 units on consumer satisfaction, product diversity has an effect of 0.302 units on consumer satisfaction and promotions has an effect of 0.265 units on consumer satisfaction. From the results of the t test and F test, it can be concluded that service quality, product diversity and promotions have a partially significant effect on consumer satisfaction, and service quality, product diversity, and promotion together have a significant simultaneous effect on consumer satisfaction.